Dynamics of di-2-ethylhexyl phthalate (DEHP) in the indoor air of an office - Li, Yatai; Xie, Di; He, Longkun; Zhao, Anqi; Wang, Lixin; Kreisberg, Nathan M; Jayne, John; Liu, YingJun (Building and Environment, 2022)
Largely limited by measurement technique, dynamics of semivolatile organic compounds (SVOCs) in the indoor air is not well understood. This study reports time-resolved measurements of airborne concentration of di-2-ethylhexyl phthalate (DEHP) in an office, using semivolatile thermal desorption aerosol gas chromatography (SV-TAG). The measurements were conducted in two separate periods during the summer-to-fall transition in 2020, each for more than 10 days. The indoor gas-plus-particle DEHP concentration varied by more than one order of magnitude in each observation period, and the temporal pattern exhibited possible influences of the indoor temperature, particle mass concentration, and outdoor DEHP concentrations. Further analysis focusing on window-closed conditions (i.e., with less outdoor contribution) reveals that the DEHP dynamics was primarily driven by variations in the indoor temperature (R2 = 0.85) during the first, warmer period (24–29 °C), and by variations in the particle mass concentration (R2 = 0.83) during the subsequent cooler period (20–23 °C). The unexpected transition of the key driving factor with change of the temperature was qualitatively justified by a simplified mechanistic model. Moreover, the particle fraction of DEHP was measured during the latter, cooler period, and it exhibited strong dependence on particle concentration, which can be fitted assuming gas-particle equilibrium partitioning, with a best-fit apparent partitioning coefficient of 0.053 ± 0.006 m3/$μ$g at 20 ± 1 °C. Overall, these results improve our understanding of real-world SVOC dynamics.
Keywords: DEHP; dynamics; Partitioning; Phthalate; temperature